Diabetic Neuropathy Evaluated by a Novel Device: Sural Nerve Conduction Is Associated with Glycemic Control and Ankle–Brachial Pressure Index in Japanese Patients with Diabetes - Hamasaki, Hidetaka; Hamasaki, Yasuteru (Frontiers in Endocrinology, 2017)
Background: Currently, no international diagnostic criteria for diabetic neuropathy (DN) have been established. Recently, a novel point-of-care sural nerve conduction device has been developed. We aimed to investigate associations between DN and clinical parameters related to the development and progression of DN by using this novel device. Methods: We conducted a retrospective observational study in patients with diabetes whose sural nerve functions were measured using DPN Check between January 2015 and October 2016. Multiple and logistic regression analyses were conducted to assess the associations of sural nerve conduction velocity (SNCV) and amplitude (SNAP) with clinical parameters related to DN. Results: A total of 740 patients were enrolled in this study. At baseline, 211 patients were diagnosed with DN by using DPN Check. The sensitivity, specificity, and positive likelihood ratio of DPN Check compared with ankle reflex as reference were 81%, 46%, and 1.5, respectively. Of these, 182 patients were followed-up for approximately 1 year to measure changes in SNCV and SNAP. Both SNCV and SNAP were inversely associated with duration of diabetes, plasma glucose levels, and hemoglobin A1c levels at baseline, whereas these were positively associated with ankle–brachial index. Logistic regression analysis revealed that poor glycemic control was associated with increased risk of reduction in both SNCV (odds ratio = 1.570; 95% CI = 1.298–1.898; p < 0.001) and SNAP (odds ratio = 1.408; 95% CI = 1.143–1.735; p = 0.001), and longer duration of diabetes was also significantly associated with an increased risk of reduction in both SNCV (odds ratio = 1.058; 95% CI = 1.032–1.084; p < 0.001) and SNAP (odds ratio = 1.049; 95% CI = 1.019–1.079; p = 0.001). Conclusion: Sural nerve functions were significantly associated with glycemic control and arteriosclerosis in patients with diabetes. DPN Check may be useful as a screening tool to identify DN in clinical practice.